(3Qi GdZdjd aj CNHGQ Hfi YHO GdLdjds - (3GHf YHO GdLdjd , eMeO Hf YHO GdLdjd Hf ZjK Hf CMeO Hf Sja GdfUQ,J (B1268 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeOkG ceG CeQ s
(3Hfh YHO GdLdjd ge edhc aRGf hGdCejQ eMeO ef MaOJge Cdag hgh HHGQjS SfI (B1268 (3g` s
(3UhQ ef NRGfI HGQjS SfI (B1345s
(3Gdajde eXdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B185 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B127s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B148 s
Keywords: (3GdJGQjNs